Empowerment: Hotel employees' perspective - Kartinah Ayupp; Then Hsiao Chung (Journal of Industrial Engineering and Management (JIEM), 2010)
An empowered worker is a knowledgeable worker. Thus, the aims of this study were to examine how empowerment is perceived by the front-line hotel employees and secondly, to identify the factors affecting empowerment within the industry. Factors such as communication, coaching, participation, training and reward were examined for any significant relationship with empowerment, along with whether the employee's socio-demographic characteristics affected their perceptions of empowerment. The findings indicated that except for gender, socio-demographic factors were not a strong influence on the diffusion of empowerment among employees. In order to ensure that the employees feel empowered, factors such as communication, coaching, participation, training and reward should be given due attention by the management. Based on the findings, implications for companies are discussed and further research is suggested.
Keywords: 650; empowerment; knowledgeable workers; front-line employees; hotel industry